Lecture Attendance Monitoring System Using Face Detection with Microcontroller - Fachmi, Zul; Saputra, Aggry; Saputra, Komang Oka (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
The implementation of the charging manually lecture attendance list can give rise to various problems in monitoring students in real, spending a lot of files, and will need a room that is spacious enough for archive files lecture attendance When in a long time. Lecture attendance system the manual it's time replaced with a computerized attendance system and biometric features. In this research will be developed the system the presence of lectures based on face recognition and identification help ATMEGA32 microcontroller to open classroom. To be able to identify students facial recognition process on an image that is by using the method of Viola-Jones. From the test results, the success rate of introduction of the application of the presence of a lecture based on the identification of facial features using the methods of the Viola-jones of 89.3%. Moreover the application can store data made the presence of student coursework in database and present information in the form of lecture attendance report